RANCANG BANGUN SALES FORCE AUTOMATION BERBASIS ANDROID DI PT. X - Fanrensen, Glenda Sogo; ,, Yulia; Wibowo, Adi (Institute of Research and Community Outreach - Petra Christian University, 2014)
The existing system of PT. X used to insert sales data manually. While in field, Sales Force noted of the order from dealer/customer manually, then later insert it into company’s database. The repetitive data copying causes bigger risk of mistyping and unreliability, because Sales Force travels for weeks. Other problem is that too many paper wasted on Sales Order and Invoice. Furthermore, PT. X needs comprehensive document support for Sales Force to fulfill customer’s need of information. In this research, Sales Force Automation (SFA) software that works online is chosen to meet the expectations. For document supply, due to the amount of documents needed, business taxonomy is made. Because the software is demanded to be easily accessed from wherever and whenever, Android is chosen as the hardware. The results obtained are various features for sales data management, such as view, add, edit, delete, and verification. The admin program supports the Sales Force work appraisal, notification, calculating Sales Force’s earnings per target ratio, Sales Force’s commission, et cetera. The SFA program supports the making of Sales Order, which is to be verified through SMS Gateway before inserted into company’s database, scheduling, et cetera.